Does thyrotoxic periodic paralysis have a genetic predisposition? A case report. (November 2018) - Rasheed, E; Seheult, J; Gibney, J; Boran, G
Thyrotoxic periodic paralysis is a rare complication of hyperthyroidism where increased influx of potassium into skeletal muscle cells leads to profound hypokalaemia and paralysis. Most cases arise sporadically in Asians; however, it is being increasingly reported in Caucasians. It is regarded as a channelopathy where a genetic and/or acquired defect in the sodium-potassium (Na/K-ATPase) pump renders it more sensitive to excess thyroid hormone in susceptible individuals. Because the clinical presentation is similar to familial hypokalaemic periodic paralysis, genes implicated in this autosomal-dominant condition became candidates for thyrotoxic periodic paralysis, particularly if they were known to have thyroid hormone-responsive elements. These include the voltage-gated calcium (CACNA1S) and sodium (SCN4A) channel genes, KCNJ18 which encodes the inwardly rectifying potassium channel Kir2.6, and subunits of the Na/K-ATPase genes. Although no single pathogenetic mutation has been identified in thyrotoxic periodic paralysis, several single-nucleotide polymorphisms in these genes have been associated with it. We describe a 27-year-old Caucasian Irish male who presented with acute onset limb paralysis and severe hypokalaemia. He was diagnosed as having thyrotoxic periodic paralysis secondary to Graves' disease based on clinical presentation, biochemical findings and rapid response to intravenous potassium. Genetic analysis identified heterozygous variants in three candidate genes: KCNJ18 (c.576G>C), SCN4A (c.2341G>A) and CACNA1S (c.1817G>A). Since these variants are not disease causing and occur at high prevalences of 50%, 2–3% and 1%, respectively, in the normal population, they do not explain the clinical phenotype in our patient suggesting that acquired environmental triggers or as-yet unidentified gene mutations remain as leading pathogenetic co-factors in thyrotoxic periodic paralysis.